Public Perception of the Use of Ecobricks as a Solution for Inorganic Waste Management Reviewed from the Principle of Benefit at the Rafflesia Sehati Foundation - Indah Permata Sari Hasibuan; Nurul Hak; Esti Alfiah (Borneo Islamic Finance and Economics Journal, 2026)
This study aims to examine public perceptions of the use of ecobricks as a solution for managing inorganic waste from the perspective of the principle of public welfare at the Sehati Rafflesia Foundation in Bengkulu. This study employs a qualitative research method with a descriptive approach. Data collection techniques were conducted through interviews, observations, and documentation. The results of the study indicate that the community holds a positive perception of the use of ecobricks. The ecobrick program is considered capable of helping to reduce plastic waste, creating a cleaner environment, and raising public awareness regarding waste management. Based on the maqashid syariah perspective, the use of ecobricks demonstrates the presence of public interest encompassing hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal. The novelty of this study lies in examining community perceptions of ecobrick utilization within a community-based institution and analyzing them through the maqashid syariah framework, an approach that has received limited attention in previous studies on ecobricks and waste management. Keywords: Public Perception, Ecobricks, Inorganic Waste Management, Public Welfare, Maqashid al-Sharia